The impact of disturbances in natural conception cycles - Gnoth, Christian; Keil, Ann-Kristin; Schiffner, Julia; Heil, Sylvia; Mallmann, Peter; Freundl, Günter; Strowitzki, Thomas (Archives of gynecology and obstetrics, 2020)
Many physicians and other healthcare professionals are often asked questions on interfering factors for conception by couples with a desire for children. Such possible disturbances include, for example, the very common minor diseases, stress and also sexual intercourse during the suspected implantation period. Non-scientifically based statements about disturbances in conception cycles, as found in many layman publications and on the internet, can strongly unsettle couples with a desire for children and force them into corset of rules of conduct. Therefore, a systematic scientific evaluation of the impact of disturbances on conception is urgently needed.
Gesehen am 21.04.2020